A severe mouse model of spinal muscular atrophy develops early systemic inflammation. (21st August 2018) - Wan, Bo; Feng, Pengchao; Guan, Zeyuan; Sheng, Lei; Liu, Zhiyong; Hua, Yimin
Abstract: Spinal muscular atrophy (SMA) is a fatal genetic disease, mainly affecting children. A number of recent studies show, aside from lower motor neuron degeneration and atrophy of skeletal muscles, widespread defects present in the central nervous system (CNS) and peripheral non-neuronal cell types of SMA patients and mouse models, particularly of severe forms. However, molecular mechanisms underlying the multi-organ manifestations of SMA were hardly understood. Here, using histology, flow cytometry and gene expression analysis in both messenger RNA and protein levels in various tissues, we found that a severe SMA mouse model develops systemic inflammation in early symptomatic stages. SMA mice had an enhanced intestinal permeability, resulting in microbial invasion into the circulatory system. Expression of proinflammatory cytokines was increased in all tissues and the acute phase response in the liver was activated. Systemic inflammation further mobilized glucocorticoid signaling and in turn led to dysregulation of a large set of genes, including robust upregulation of FAM107A in the spinal cord, increased expression of which has been implicated in neurodegeneration. Moreover, we show that lipopolysaccharide challenge markedly suppressed survival of motor neuron 2 exon 7 splicing in all examined peripheral and CNS tissues, resulting in global survival of motor neuron level reduction. Therefore, we identified a novel pathological mechanism in a severe SMA mouse model, which affects phenotypic severity through multiple paths and should contribute to progression of broad neuronal and non-neuronal defects.